H2A.Z is dispensable for both basal and activated transcription in post-mitotic mouse muscles. Issue 9 (8th April 2020) - Belotti, Edwige; Lacoste, Nicolas; Simonet, Thomas; Papin, Christophe; Padmanabhan, Kiran; Scionti, Isabella; Gangloff, Yann-Gaël; Ramos, Lorrie; Dalkara, Defne; Hamiche, Ali; Dimitrov, Stefan; Schaeffer, Laurent
Abstract: While the histone variant H2A.Z is known to be required for mitosis, it is also enriched in nucleosomes surrounding the transcription start site of active promoters, implicating H2A.Z in transcription. However, evidence obtained so far mainly rely on correlational data generated in actively dividing cells. We have exploited a paradigm in which transcription is uncoupled from the cell cycle by developing an in vivo system to inactivate H2A.Z in terminally differentiated post-mitotic muscle cells. ChIP-seq, RNA-seq and ATAC-seq experiments performed on H2A.Z KO post-mitotic muscle cells show that this histone variant is neither required to maintain nor to activate transcription. Altogether, this study provides in vivo evidence that in the absence of mitosis H2A.Z is dispensable for transcription and that the enrichment of H2A.Z on active promoters is a marker but not an active driver of transcription.